Pengaruh Lama Pemberian Distres Kronis terhadap Aktivitas Sel Osteoklas pada Tulang Alveolar Tikus Sprague-Dawley (The Effect of Chronic Distress Duration to Osteoclast Cells Activity in Alveolar Bone of Sprague-Dawley Rats) - Maria Devitha; Didin Erma Indahyani; Happy Harmono (Pustaka Kesehatan, 2015)
Excessive and prolonged distress (chronic) can cause damage to periodontal tissues, specifically alveolar bone resorption. Alveolar bone resorption is caused by osteoclast cells activity. The purpose of the research is to determine effect of chronic distress duration to osteoclast cells activity in alveolar bone of male Sprague-Dawley rats attain the age of 3-4 months. The rats were given an electric shock stressor (Electrical Foot Shock) as distress chronic for 7, 14, and 28 days. Stressors were given for 30 minutes at 9 a.m every day during the treatment period. The amount of electrical current is 2-8 mA, 48 V voltages and 0.5 Hz frequency. Osteoclasts activity were observed histologically with 400x magnification using osteoclast Bone Interface (OBI) Index by dividing the length of howship's lacunae with osteoclasts. Result showed signifficant difference at 0.00 (p<0.05) beetwen the variable.Activity of osteoclasts in alveolar bone of Sprague-Dawley rats which were exposed to the stressor is increased when compared to the group that were not exposed to electrical shock stressor, but at day 14 decreased when compared to the other treatment groups. Keyword : chronic distress, osteoclast activity, alveolar bone